Aplikasi Sistem Informasi Administrasi Pada UD. Terang Jaya Abadi - Indra Setiawan; Silvia Rostianingsih (Jurnal Infra, 2020)
The proses of making this information system includes data on stock items that function to store data items. Sales transactions serves to help sales transactions to customers. Purchase transactions function to help purchase transactions with suppliers. Transaction sales and purchase returns function to help return items that are not appropriate. Transaction reports serve to make it easier for owners to review data.This information system is built using the PHP programming language, and the database uses MySQL.Based on testing, the system can carry out transaction activities such as sales transactions, purchase transactions, returns transactions and sales report activities of UD. Terang Jaya Abadi.